2(4x+7)=3+2x+2

Simple and best practice solution for 2(4x+7)=3+2x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4x+7)=3+2x+2 equation:


Simplifying
2(4x + 7) = 3 + 2x + 2

Reorder the terms:
2(7 + 4x) = 3 + 2x + 2
(7 * 2 + 4x * 2) = 3 + 2x + 2
(14 + 8x) = 3 + 2x + 2

Reorder the terms:
14 + 8x = 3 + 2 + 2x

Combine like terms: 3 + 2 = 5
14 + 8x = 5 + 2x

Solving
14 + 8x = 5 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
14 + 8x + -2x = 5 + 2x + -2x

Combine like terms: 8x + -2x = 6x
14 + 6x = 5 + 2x + -2x

Combine like terms: 2x + -2x = 0
14 + 6x = 5 + 0
14 + 6x = 5

Add '-14' to each side of the equation.
14 + -14 + 6x = 5 + -14

Combine like terms: 14 + -14 = 0
0 + 6x = 5 + -14
6x = 5 + -14

Combine like terms: 5 + -14 = -9
6x = -9

Divide each side by '6'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| 4x^2+2x-6= | | (5y-1)(23y-1)= | | 5x^2=27 | | x^2+3x^2=x^2 | | -11x+9=-12+13 | | 6x-8=3x | | 1x-9= | | 4x-y=-10 | | t(t-2)-3t(t-2)=0 | | t(t-2)-3t(t-3)=0 | | 6(-x+4)=9 | | -2(5y+1)=4(y+6)-2 | | h=-16t^2+68t | | 5y+5=2y+10 | | 64=2(5x+2)+(3x-2) | | 2a^2-81=0 | | 1x+3x+-18x=0 | | 5x=2-2x | | x-3x+-18x=0 | | -4x^2+3x=1 | | 3(h)+6=2(h)-14 | | 3(-20)+6=2(-20)-14 | | 3x-2y+5z+au=0 | | -4x-5x=18 | | 6n^2=15+12n | | 2-4(-6)-7=3+2(-6)+4 | | 12w-5=19+6w | | 4m^2-57=7m | | 10x^2+9=379 | | -2x^2+2=3x | | 11x=8x-15-6x | | 3p^2+6=216 |

Equations solver categories